2001
DOI: 10.1002/chin.200114214
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis, NMR and Conformational Studies of Fucoidan Fragments. Part 1. Desulfated 2,3‐ and 3,4‐Branched Trisaccharide Fragments and Constituting Disaccharides.

Abstract: Synthesis, NMR and Conformational Studies of Fucoidan Fragments. Part 1. Desulfated 2,3-and 3,4-Branched Trisaccharide Fragments and Constituting Disaccharides. --(KHATUNTSEVA, ELENA A.; USTUZHANINA, NADEZHDA E.; ZATONSKII, GEORGIJ V.; SHASHKOV, ALEXANDER S.; USOV, ANATOLY I.; NIFANT'EV, NIKOLAY E.; J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 1 publication
0
8
0
1
Order By: Relevance
“…6 In this paper we present the results of these reactions and theoretical calculations of plausible intermediates which demonstrate a larger influence on the efficiency of ␣-fucosylation of a benzoyl group at O-3 in a fucosyl donor than of that at O-4.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…6 In this paper we present the results of these reactions and theoretical calculations of plausible intermediates which demonstrate a larger influence on the efficiency of ␣-fucosylation of a benzoyl group at O-3 in a fucosyl donor than of that at O-4.…”
Section: Introductionmentioning
confidence: 98%
“…In the course of the synthesis of fucoidan fragments 6 we investigated the glycosylation of allyl 3,4-di-O-isopropylidene-␣-L-fucopyranoside 9 7 by 3-O-and 3,4-di-O-benzoylated 2-O-benzyl-L-fucopyranosyl bromides 6 and 7. 6 In this paper we present the results of these reactions and theoretical calculations of plausible intermediates which demonstrate a larger influence on the efficiency of ␣-fucosylation of a benzoyl group at O-3 in a fucosyl donor than of that at O-4.…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous works devoted to the synthesis of oligosaccharides related to blood group antigens, there are only a few papers dedicated specifically to the synthesis of A trisaccharide derivatives [ 4 , 5 , 6 , 9 ]. Herein, we report on the assembly of spacered A trisaccharide 1a and its biotinylated derivative 1b , making use of the new galactose block 4 , which bears a set of convenient temporary protecting groups permitting selective liberation of HO-groups as well fucosyl donor 5 [ 18 , 19 ] and bicyclic 2-azido-2-deoxy-selenogalactoside 10 [ 20 ] containing stereo-controlling O-protecting groups, which favor the required α-(1,2- cis )-glycosylation. A bulky 4,6-O-(di-tert-butylsilylene)-protecting group at O-4 and O-6 was used to prevent the formation of undesirable β-glycosylation products [ 21 ] while a 3-O-benzoyl group was introduced to provide α-stereocontrol through remote anchimeric participation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2000 this group has synthesized a broad series of mono-, di-, tri-, tetra-, hexa-, octa-, dodeca-, and hexadeca-α-L-fucosides (see Figure 1.2 C) bearing various glycosidic linkage patterns, branching, and sulfation degree and patterns [35][36][37][38][39][40][41][42]. Recently, this group synthesized a fragment from the brown seaweed Chordaria flagelliformis containing an α-L-fucofuranosyl unit (see Figure 1.2 D), which is unusual compared to the α-L-fucopyranosyl conformation that constitutes the vast majority of the L-fucosides found in fucoidan [43].…”
Section: Fucoidan-mimetic Oligosaccharidesmentioning
confidence: 99%
“…Recently, this group synthesized a fragment from the brown seaweed Chordaria flagelliformis containing an α-L-fucofuranosyl unit (see Figure 1.2 D), which is unusual compared to the α-L-fucopyranosyl conformation that constitutes the vast majority of the L-fucosides found in fucoidan [43]. The conformation of all of these fucosides have been carefully studied by NMR spectroscopy, but their biological properties have remained almost entirely unpublished [35][36][37][38][39][40][41][42][43]. As an exception a recent study showed that a fully sulfated α(1→3) octa-L-fucoside displayed no or decreased antibacterial phagocytic activity compared to fucoidan of larger molecular weights from natural sources [44].…”
Section: Fucoidan-mimetic Oligosaccharidesmentioning
confidence: 99%